Flower and fruit: morphology, ontogeny, phylogeny, function and ecology ; with 3 tables - Leins, Peter; Erbar, Claudia (Schweizerbart Textbooks, 2010)
Cover -- Title -- Copyrights -- Contents -- Preface -- Beforehand some thoughts on the origin and the important role of the flowers in the life cycle of plants -- Early angiosperm flowers - the fossil Archaefructus -- Short description of an angiosperm flower - some basic terms -- The genetic approach to the floral organ determination - from the A-B-C model to the A-B-C-D-E model -- Differential growth and organ delimination -- Number and arrangement of floral organs in the flowers -- Spiral flowers with high and indefinite organ number -- Transition to whorled (cyclic) flowers -- Whorled (cyclic) flowers -- Floral symmetry -- The perianth -- Perigone, calyx, corolla -- Aestivation -- Epicalyces -- Tubular formations in the perianth - syntepaly, synsepaly, sympetaly -- The androecium -- Ontogeny of an individual stamen -- Deviating anther structures -- The pollen grains -- Stamen fascicles, fascicled androecia -- The cabinet of curiosities -- The staminode concept -- The gynoecium -- Ontogeny of an individual carpel -- The variation of the proportions -- Choricarpy and coenocarpy -- The internal design of coenocarpous gynoecia -- Pollen tube transmitting tissue and compitum -- The ovules -- The floral axis -- Stalk-like elongations of the axis (floral internodes) -- Cup-shaped formations (floral cups and floral tubes) -- Hypanthial ovaries with unusual internal designs -- The inferior ovary in the cucumber family -- Unusual placentations in connection with intercalary growth processes in the floral axis -- Nectaries -- Different sites of floral nectaries -- Nectary organs -- Extrafloral nectaries -- Floral diagrams -- Inflorescences -- Important flower functions and the relevant adaptations -- The problem of hermaphroditism in flowers or: how to prevent inbreeding -- Dichogamy -- Herkogamy -- Separation of sexes (dicliny) -- Heterostyly.